A efetividade participativa dos conselhos gestores de políticas públicas: um estudo sobre o Conselho Estadual das Cidades da Bahia - OLIVEIRA JÚNIOR, João Pereira (2015)
This thesis is the analysis of the State Council of Bahia Cities (CONCIDADES-BA) as an instrument of participation in state public policies of urban development. First, the research sought to highlight the main theoretical foundations on democratic principles and citizen participation, exposing the different approaches in the literature on the subject. Then this study sought to show the inherited share instruments of the Constitution of 1988. After we brought reports of institutional experience and social mobilization around participation. Following promote a descriptive approach and CONCIDADES-BA's criticism. This research has a quantitative and qualitative profile of participant and exploratory based on ethnographic method outlined from consultations on secondary sources and complemented by primary information based on the analysis of the minutes, the participant observation of Council meetings and a questionnaire together with the advisors. As for the theoretical treat the issue of effectiveness of participation by the authors: Elenaldo Teixeira with analytical categories of participatory effectiveness: Representative, Parity and feasibility and Sheri Arnstein with concept of scale of participation, as well as the experience / concept of the New collective Citizens approached by Deborah Nunes and Ivan Maltcheff. Based on this theoretical framework we made the crossing of these concepts and hypotheses to the results empirically with field research. We conclude suggesting a readjustment in the process of participation in the formulation and monitoring of public policies in the field of urban development in the state of Bahia.